Elevated Admission Cardiac Troponin I Predicts Adverse Outcomes of Acute Type B Aortic Dissection after Endovascular Treatment - Zhao, Kaiwen; Zhu, Hongqiao; Zhang, Lei; Liu, Junjun; Pei, Yifei; Zhou, Jian; Jing, Zaiping (Frontiers in Surgery, 2022)
Background: There is a lack of evidence about the predictive role of serum cardiac troponin I (cTnI) on the long-term adverse outcomes of acute type B aortic dissection (aTBAD) patients after thoracic endovascular aortic repair (TEVAR). In this study, we identified whether cTnI was an independent risk factor of 5-year adverse outcomes for aTBAD patients after TEVAR. Methods: We reviewed consecutive aTBAD patients without previous heart disease who were admitted for TEVAR. Total study population were divided into the cTnI(+) group (≥0.03 ng/ml) and the cTnI(-) group (<0.03 ng/ml) according to the time-dependent receiver operating characteristic curve analysis. The differences in clinical characteristics, operative details and clinical outcomes were compared between the two groups. Results: There was no difference in age and male prevalence between the two groups. Compared with the cTnI(-) group, the incidence of chronic kidney disease was higher in patients with cTnI ≥0.03 ng/ml. In addition, the cTnI(+) group presented with more frequent premature beats and non-myocardial-infarction ST-T segment changes. In terms of laboratory examinations, white blood cell counts, neutrophil counts, serum D-dimer and serum fibrin degradation products were increased in the cTnI(+) group while lymphocyte and platelet counts were decreased in these patients. Patients with elevated cTnI suffered from increased risks of 5-year aortic-related adverse events (hazard ratio, HR =1.822, 95% confidence interval, CI: 1.094-3.035; P = 0.021) and all-cause mortality (HR =4.009, 95% CI: 2.175-7.388; P <0.001). Conclusion: Among aTBAD patients without previous heart disease, preoperative elevated cTnI identified patients at an increased risk of long-term adverse outcomes after TEVAR.